Karakterisasi FTIR pada Studi Awal Penumbuhan CNT dengan Prekursor Nanokatalis Ag dengan Metode HWC-VHF-PECVD: Ajeng Eliyana, Toto Winata - Ajeng Eliyana Ajeng Eliyana; Toto Winata Toto Winata (Jurnal Fisika dan Aplikasinya, 2017)
The study of CNT growth has been done by using silver (Ag) nanocatalyst as a precursor guide on the corning glass 7059 substrate by the use of the evaporation method. Thegrowth were done by varying deposition times for 50, 25, and 14 seconds, then followed by the annealing process at temperature of 400C for 4 hours. The characterization of Ag nanocatalyst morphologywere done by using Scanning Electron Microscope (SEM) and Energy Dispersive Analysis X-ray (EDX). The CNT thin filmsof growth on the Ag nanocatalyst substrate was then deposited by the Hot wire Cell-Very High Frequency Plasma Enhance Chemical Vapour Deposition (HWC-VHF-PECVD) method,at deposition temperature of 275C and pressure of 300 mTorr. The rf power was varied from 8 to 20 watts, with deposition time for 60 minutes.The 99.999% methane (CH4) gas was used as Carbon sources. The hydrogen gas (H2) was used to etch the oxide layer formed during the pre-deposition process. The CNTdiamater and length for on the Ag/CG 7059 were 250 to 393 nm and 309 to 376 nm, respectively, for the cluster distribution of particles. Meanwhile, for the tubes particle (CNT) the diameter and length were 125 nm and 1.650 to 2.989 µm, respectively. At the rf power of 8 and 10 watts,the CNTs were vertical and horizontal shape on the substrate surface. The CNTthin films growth were further characterized using Fourier Transform Infra Red (FTIR). The rf power of 8 and 10 watts results showed the C=C and C-C cluster, and C-C cluster at 20 watts.